2006
DOI: 10.1002/app.25324
|View full text |Cite
|
Sign up to set email alerts
|

Influence of incorporating CaCO3 into room temperature vulcanized silicone sealant on its mechanical and dynamic rheological properties

Abstract: Silicone sealants with low modulus and high elongation were prepared by using ketoxime silane as chain extender agent, and a novel silane coupling agent acting as adhesion promoting agent was synthesized. Mechanical properties of vulcanized polydimethylsiloxane (PDMS) filled with large amounts of carbonate calcium (CaCO 3 ) and dynamic viscoelastic properties of unvulcanized samples were investigated through electronic multifunctional tensile tests, dynamic mechanical analyzers, and dynamic rheological measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 93 publications
0
21
0
Order By: Relevance
“…In the filler structure models, it has been widely accepted that when the particle loading is above percolation threshold, a secondary network structure will form. [22][23][24][25][26][27][28] Because of the interactions between the particles as well as particles and polymer matrix, there is either a particle-particle or particle-matrix ''network'' formation. Therefore, the filled polymers exhibited some particular rheological properties due to the different structures.…”
Section: -21mentioning
confidence: 99%
“…In the filler structure models, it has been widely accepted that when the particle loading is above percolation threshold, a secondary network structure will form. [22][23][24][25][26][27][28] Because of the interactions between the particles as well as particles and polymer matrix, there is either a particle-particle or particle-matrix ''network'' formation. Therefore, the filled polymers exhibited some particular rheological properties due to the different structures.…”
Section: -21mentioning
confidence: 99%
“…Several researchers have already prepared polymer nanocomposites using the micron-sized and nanosized CA inorganic filler. [2][3][4][5][6][7][8][9][10][11][12] To avoid agglomeration, especially when CA nanofiller is used, the surface energy resulting from filler-filler interactions needs to be lowered via coating the filler surface with carboxylic monomers like stearic acid. 2,3,6,10 The nanosized CA has occasionally been used to prepare elastomeric nanocomposites with satisfactory thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the incorporation of fillers into rubbers results in remarkable changes in the viscoelastic behavior of these materials. [2][3][4] Recently, calcium carbonate (CaCO 3 ) plays an increasingly important role and has been extensively applied in rubbers, plastics, sealants and pigments industry due to its remarkable benefits such as abundant raw material resource, low price, stable properties and simple processing procedure. [5][6] It can not only reduce the manufacturing cost but also impart enhanced performances such as tensile strength, modulus, elongation at break, thixotropy and storage stability to the elastomeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…10) Depending on whether inter-particle attractions or interactions between particles and polymer chains are stronger or not, there is either a particle-particle or particlematrix network formation. 3) In addition, some studies concerning the mechanism of reinforcement by filler particles have been reported recently. [11][12][13][14] As 3)…”
Section: Introductionmentioning
confidence: 99%